Effect of Total Members and Current Ratio on the Rest of Cooperative Business Result - Firdaus Firdaus (Yayasan Ilomata, 2020)
This study aims to analyze the effect of variable number of members and current ratio on the remaining business results (SHU). The sample used is all data for the time series period 2012-2018. The data used are secondary data and the method used is multiple linear regression analysis with the help of SPSS Version 23 program to obtain the influence of the independent variables with the dependent variable. The results showed that the number of members had a positive and significant effect on the residual results of operations, the current ratio had a negative and significant effect on the residual results of operations.